Incidence, Disease Spectrum, and Outcomes of Tuberculous Meningitis in South African Children: The Initial Impact of COVID-19 - Victoria E. Namukuta; Mariette Smith; Danite Bester; Magriet van Niekerk; Regan Solomons; Ronald van Toorn; Hendrik Simon Schaaf; James A. Seddon; Helena Rabie; Mary-Ann Davies; Anneke C. Hesseling; Karen du Preez (Tropical Medicine and Infectious Disease)
Tuberculous meningitis (TBM) is a very severe form of childhood tuberculosis (TB), requiring hospitalisation for diagnosis. We investigated trends in admission, disease spectrum, outcomes, and healthcare system factors in children with TBM managed at a tertiary referral hospital in Cape Town, South Africa. We conducted a retrospective cohort study of children (<13 years) with TBM admitted from 2017 to 2021. An innovative surveillance algorithm was used to identify all possible TBM episodes using integrated electronic health data. Episodes were clinically verified and data were extracted using medical records. A total of 263 children (median age 2.2 years; IQR: 1.1–5.1), 17 (6.5%) living with HIV were admitted with TBM during 2017 to 2021. There was a significant reduction in TBM admissions during the COVID-19 pandemic (IRR: 0.57, 95% CI:0.39–0.84), particularly in children < 2 years (IRR: 0.31, 95% CI: 0.15–0.62). BCG vaccination was documented in 137/263 (52.1%) and 10/87 (11.5%) eligible children who initiated TB preventive therapy. During the pandemic, children with TBM were significantly more likely to be living with HIV (aOR: 4.01, 95% CI: 1.39–11.62). COVID-19 was associated with a significant reduction in the number of young children admitted with TBM. Many missed opportunities to prevent TBM were identified regardless of COVID-19. Paediatric TBM surveillance is a useful marker to monitor epidemiological trends.